Assessment and Selection of CMIP6 Climate Models: Application to the Budhigandaki River Basin (BGRB), Nepal - Lamichhane, Shankar (Himalayan Journal of Applied Science and Engineering, 2025)
The most representative CMIP6 Global Climate Models for predicting future climate conditions in the Budhigandaki River Basin (BGRB) are found using an advanced envelope selection method. For each scenario (SSP2-4.5 and SSP5-8.5), four GCMs that best replicate the basin's historical climate and forecast future changes were selected by combining envelope-based range coverage, historical performance assessment, and climate extreme analysis. EC-Earth3-CC, MIROC6, MPI-ESM1-2-LR, and MRI-ESM2-0, representing the Warm-Wet, Warm-Dry, Cold-Dry, and Cold-Wet extremes for SSP2-4.5. For the corresponding climate conditions, IPSL-CM6A-LR, MRI-ESM2-0, GFDL-ESM4, and INM-CM5-0 under SSP5-8.5. These models were selected because they accurately simulated past climatic trends throughout BGRB. The mean air temperature in the basin is predicted to rise by 2.92°C to 3.22°C under SSP2-4.5 and by 3.66°C to 7.07°C under SSP5-8.5 scenarios by the end of the twenty-first century. Forecasts of precipitation show increment with ranges of 0.08% to 17.55% (SSP2-4.5) and 5.00% to 38.97% (SSP5-8.5). These models were chosen because they accurately simulated past climatic trends throughout BGRB. The BGRG’s impact assessments and adaptation planning are firmly based on the explicit identification of these models, which faithfully replicate both mean and extreme climate behaviours.